Tampon Vital Pulp Therapy in the Management of Excessive Haemorrhage in Inflamed Pulps: A Hypothesis - Parhizkar, Ardavan; Roghanizadeh , Leyla; Asgary , Saeed (Iranian Endodontic Journal, 2023)
Current principles in vital pulp therapy (VPT) modalities emphasise the importance of haemostasis and normal clotting in the achievement of successful treatment outcomes. However, the aforementioned notion could be challenged by the new and recent emerging evidence; suggesting that prolonged or excessive bleeding/haemorrhage (PB) in cases of intensly inflamed pulps, conventionally infamous as irreversible pulpitis (IP), may not impede the healing potential of the remaining dental pulp tissue following VPTs using endodontic biomaterials. “Tampon VPT (tVPT)” may be considered a treatment approach for the management of stated IP cases; characterised by severe pulpal inflammation and delayed clotting process. The presented hypothesis evaluates clinical studies, experimental research and molecular impacts on clotting within the inflamed dental pulp, so as to explore the efficacy as well as the safety of tVPT as a viable treatment option. Latest clinical investigations have reported positive outcomes with tVPT; even in the presence of IP with PB. It has been shown that inflamed dental pulp tissues exhibit molecular impacts on the clotting cascade, which may contribute to the delayed clotting process. Nonetheless, the healing capacity of the dental pulp is not negatively affected by hyperaemia. Additionally, enhanced blood flow in the inflamed pulpal tissues may be associated with improved healing and boosted hard tissue formation. Moreover, tVPT could possibly promote pulpal healing and/or regeneration through continuing the presentation of essential nutrients, e.g. oxygen, and growth factors to the injured tissue. Furthermore, increased blood flow may facilitate the recruitment of immune and reparative cells; promoting tissue repair and encouraging the formation of dentinal bridge(s) after VPTs. Consequently, the state-of-the-art research and their findings could support the hypothesis that tVPT may effectively manage IP cases with PB and contribute to favourable outcomes.